Polityka karna w zakresie orzekania kary grzywny - Antkowiak, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper is an analysis of the penal policy with regards to adjudicating fines and the importance of the penalty in the structure of imposed sanctions over the years 1970–2012. It presents the percentage of fines against the background of all convictions under a final and valid court judgments within the duration of both the current Penal Code and the former one dated 1969. The study also indicates the issue of the intensity of fines in the years 1970–2012.
Keywords: fine; policy; punitive definition; intensity; effectiveness